Attempts for radical innovation in the big emerging countries: the case of China. (18th September 2006) - Yu, Jiang; Tan, Kim Hua
This paper tries to gain a better understanding of the process of the radical innovations in the big emerging countries and to find key dynamics that influence such an innovation process under a favourable institutional environment. In observing the evolution and initial success of China's 3G standard, the desire to exchange resources between the local and global partners, in terms of internationalisation, is found critical to drive the radical innovation process. The effective matching and co-evolving within the collaborative network becomes essential to develop the new technology-based industries. Therefore, building effective partnership mechanism with institutional support is more likely to lead the indigenous manufacturing firms to the success of the radical innovation.